2015
DOI: 10.1111/jam.12937
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective optimization of real-time PCR-based detection of Campylobacter and Salmonella with inhibitor tolerant DNA polymerases

Abstract: This work exemplifies a cost-effective strategy for optimizing real-time PCR-based assays. However, a DNA polymerase suitable for one assay and sample type is not necessarily optimal for other assays or sample types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The highly specific identification of pathogens is enabled by PCR in a few hours. However, Fachmann et al reported that the limit of detection (LOD) of real-time PCR-based detection of S. enterica was 10 3 CFUs·mL −1 [ 9 ], which is a higher concentration than that of the conventional culture method. In addition, it is necessary to reduce the amount of PCR reagents used to assay many samples because PCR reagents are expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The highly specific identification of pathogens is enabled by PCR in a few hours. However, Fachmann et al reported that the limit of detection (LOD) of real-time PCR-based detection of S. enterica was 10 3 CFUs·mL −1 [ 9 ], which is a higher concentration than that of the conventional culture method. In addition, it is necessary to reduce the amount of PCR reagents used to assay many samples because PCR reagents are expensive.…”
Section: Introductionmentioning
confidence: 99%
“…These samples are challenging for rapid PCR-based detection, as certain PCR inhibitors are expected and have to be removed prior to detection, e.g., heme from blood (23), myoglobin from tissue (24), and fat (25). PCR inhibition can be relieved by using a DNA polymerase more tolerant to inhibitors (26) or by adding PCR facilitators to the PCR master mix (27), but often a combination with a sample preparation step is needed in order to generate a PCR-compatible sample. Studies have shown that PCR inhibitors can be reduced by physical, biochemical, immunological, and physiological sample preparation methods.…”
mentioning
confidence: 99%
“…and, of course, combinations of both can be adapted. As with Fachmann and colleagues [ 19 ], we originally desired solely a cost-effective polymerase exchange without performing too many optimizations other than specific necessities such as the initial denaturation of the AmpliTaq Gold. However, this extended denaturation step appears to be insufficient for satisfactory amplification and the performance of most other polymerases was also poor ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Buzard and colleagues compared ten different qPCR mastermixes with four bacterial assays and demonstrated differences between the mastermixes and assays [ 29 ]. Additionally, Fachmann et al, for cost-effective qPCR optimization, compared 16 polymerases with two bacterial assays and different sample types and concluded that the choice of the appropriate polymerase depends upon the assay, question and sample type [ 19 ]. Likewise, unequal performances of diverse assays using different mastermixes were demonstrated recently [ 30 ].…”
Section: Discussionmentioning
confidence: 99%